Otimização estrutural de um triciclo adaptado para Frame Running (PETRA) projetado com modelagem paramétrica - Santos, Frederico Sousa (2024)
Frame Running (PETRA) is a para-athletics practiced by athletes with Cerebral Palsy. It involves using a tricycle-like equipment but instead of using a pedal system, athletes propel themselves with their feet along the track. This adapted sport still in the implementation phase in Brazil and in the context of sport dissemination, representatives from the Brazilian Paralympic Committee contacted the Professor Henner A. Gomide Mechanical Projects Laboratory (LPM) and the Brazilian Center of Reference in Technological Innovations for Paralympic Sports (CINTESP.Br), claiming that one of the models currently used for sport initiation presented constant breakages and instability during races. Thus, a CAD model of the current frame was built, and structural simulations were performed using the finite element method to investigate the causes of the reported problems. Results indicated that the frame was inadequately designed, and critical points coincided with reported breakages. Subsequently, a fully parameterized new geometry was proposed and compared with the current model through simulation, implementing an optimization routine to reduce weight and increase equipment resistance, thereby enhancing athlete performance and safety. Finally, a prototype was manufactured, and usability tests with athletes were performed to validate the project in a relevant environment. Key findings included a significant 70% improvement in stress and deformation levels compared to the reference structure, translating into enhanced race times for the evaluated athletes.